FINANCIAL DETERMINANTS OF EDUCATIONAL RESOURCES MANAGEMENT FOR ENHANCING STUDENTS’ PERFORMANCE IN SECONDARY SCHOOLS IN VIHIGA COUNTY, KENYA - Ayoti, Caroline; Koteng, Dr. Grace; Odhiambo, Dr. Raphael Ongunya (IJRDO - Journal of Applied Management Science, 2016)
Resource utilization is an integral part of the overall management of the school.Education in a school is explored by provision of resources, their maximum utilizationand management. Proper management of resources enhances students’ performance andachieves the educational objectives. The success or failure of any organization, businessor enterprise depends highly on proper management of human and material resources.The purpose of this study was to establish the financial determinants of management ofeducational resources for enhancing students’ performance in secondary schools inVihiga County. A descriptive survey design was adopted. The study populationcomposed of 112 head teachers, 1,120 teachers, 4,480 students and 9 County QualityAssurance and Standards Officers. Simple random sampling method, stratified samplingtechnique, saturated sampling technique and purposive sampling method were used toselect samples. Questionnaires and in-depth interview guides, observation schedules anddocument analysis were used to collect data. Reliability of instruments was determinedthrough a pilot study conducted in 3 secondary schools. Results of reliability of theinstruments were assessed using Pearson’s product moment correlation coefficient test.Content validity was established by availing instruments to supervisors. Qualitative datafrom interviews was transcribed and reported according to emerging themes, categoriesand sub-categories while quantitative data was analyzed using descriptive statistics suchas frequency counts, means and percentages. Pearson’s product moment correlationcoefficient was used to establish relationships between variables. Findings of the studyrevealed that the inadequacy of financial resources in schools in Vihiga County had anegative impact on acquisition of relevant and adequate educational resources and thisalso impacted negatively on performance of students in KCSE exams. From the study itis concluded that procurement of resources mainly depend on fee collection, proceedsfrom income generating activities, fund raising activities (Harambee), bursaries,